Spatial patterns in the taxonomic and dietary diversity of New Zealand rocky reef fishes : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Biological Sciences at Massey University, Albany, New Zealand - Howarth, Odette Ruth (Massey University, 2018)
Latitudinal gradients of high species richness from the tropics declining towards the poles are well documented for many terrestrial and marine species. However, these broad scale patterns of numbers of species observed don’t inform as to how related these species are, or how they use food resources. By understanding taxonomic relationships between observed species I can predict how resilient these assemblages are and how environmental processes impact their distribution. Dietary diversity between species describes patterns related to mechanisms of food availability and preference of habitats or environmental niches. Marine fishes are speciose and well known taxonomically, and so comprise a useful system for studying broad-scale patterns in biodiversity. Here I examined five indices of diversity—species richness, average taxonomic distinctness, variation in taxonomic distinctness, average diet diversity and variation in diet diversity—using a historical dataset on the presence/absence of rocky reef fishes spanning most of New Zealand. I modelled these indices using boosted regression trees and mapped their distributions to the coastline at a 1km scale resolution. Additionally, I developed a new quantitative methodology to classify coastal, rocky reef fishes into homogenous diet guilds using hierarchical clustering of nine broad food items and SIMPROF multivariate analysis and modelled species richness of three of the diet guilds (herbivore, invertivore and piscivore/benthic invertivores) using boosted regression trees. This research has broadened our understanding of patterns of fish diversity, spatial patterns in diversity of diets in coastal rocky reef fishes in New Zealand. I found the indices of overall species richness, species richness of herbivores and invertivores, and average taxonomic distinctness to be highly correlated with increased wintertime sea-surface temperature indicating a latitudinal gradient to their distributions. Decreased turbidity increased average dietary diversity and species richness of the piscivore/benthic invertivore guild. Average fetch or exposure had a positive relationship with variation in diet diversity and a negative relationship with variation in taxonomic distinctness. Of secondary importance I found the indices of overall species richness, species richness of invertivores, average taxonomic distinctness and variation in diet diversity to be adversely affected by increased turbidity. Variation in taxonomic distinctness and species richness of the herbivore diet guild increased with variable and increasing salinity (respectively) while average diet diversity increased with exposure. Lastly the piscivore/benthic invertivore guild had a positive relationship with increased wintertime sea-surface temperature. Overall I found broad and fine scale environmental processes affected the species richness and taxonomic diversity of NZ reef fishes as did food availability, resource use and habitat preferences.
Keywords: Reef fishes; New Zealand; Classification; Food; Effect of temperature on; Effect of turbidity on; Marine biological diversity; Mathematical models; Spatial analysis (Statistics)